Get a kick out of this: the spectrum of knee extensor mechanism injuries. Issue 2 (21st October 2010) - Tuong, Betty; White, Jeremy; Louis, Luck; Cairns, Robyn; Andrews, Gordon; Forster, Bruce B
Abstract : At the end of this article, the reader should be able to (1) recognise normal anatomy and anatomical variants of the extensor mechanism of the knee on various imaging modalities, including plain film, ultrasound and MRI; (2) diagnose a broad spectrum of EM injuries in adult and paediatric patients including patellar and quadriceps tendinopathy, Osgood–Schlatter disease, Sindig–Larsen–Johansson syndrome, chondromalacia patellae and patellar fractures on various imaging modalities; and (3) appreciate the important role of imaging in the diagnosis of musculoskeletal injuries.